Treatment of proximal superficial caries lesions on primary molar teeth with resin infiltration and fluoride varnish versus fluoride varnish only: Efficacy after 1 year (2010)
This split-mouth study aimed to assess the efficacy of resin-infiltrated lesions covered by fluoride varnish (FV) versus FV treatment only of proximal lesions on deciduous molar teeth. The study lasted for 1 year. Children with 2 or more superficial proximal lesions on deciduous molar teeth detected on bitewing radiographs were included. After written parental consent, two lesions in each of 50 children were randomly allocated to one of two treatments: resin infiltration followed by FV (2.26% F) application (test lesion) versus only FV (control lesion). The ICDAS scores of the selected lesions were recorded by 2 clinicians before the treatments (weighted kappa for inter- and intra-examiner agreement >0.79). FV was applied to both test and control lesions 6 and 12 months after the first treatment. After 1 year ICDAS scores were obtained for 42 children and radiographs for 39. One external examiner not familiar with the study scored the radiographs twice (weighted kappa 0.88). Baseline mean age of the children was 7.17 ± (SD) 0.68 and mean def-s was 8.1 ± (SD) 6.9. After 1 year the ICDAS scores of 31% of the test lesions and 67% of the control lesions had progressed (p < 0.01). Radiographically, 23% of the test lesions and 62% of the control lesions had progressed (p < 0.01). Thus, the clinical and radiographic therapeutic effect of both resin infiltration/FV over FV alone was >35% and significant. To conclude, resin infiltration in conjunction with fluoride varnish seems promising for controlling proximal lesion progression on deciduous molar teeth.